The digital divide in rural schools: a case study - José Sastre Reyes (Universidad de Málaga, 2019)
The present research focuses on the existing problems regarding the lack of resources and training in the use of ICT in the Andalusian rural school. The research was carried out at Alto Almanzora, a rural public school located in Armuña de Almanzora, a town in Almería. The methodology used was a qualitative approach and, according to the characteristics of this research, it was necessary to opt for a case study. The sample consisted of a total of 15 students and a teacher. For data collection, two semi-structured interviews were planned, directed on the one hand to the students and on the other hand to the teacher. The results showed that the students do not benefit from specific training proposals on the use of ICT, only in the subjects of Digital Culture and Citizenship. The teacher has a low level of digital teaching competence and does not receive specific training on the use of ICT with students. And, finally, the technological resources at the school can only be used by fifth and sixth grade students, so a lack of resources and training is evident in most of the educational levels at the school.